Modulation of intestinal tight junctions by Zonula occludens toxin permits enteral administration of insulin and other macromolecules in an animal model. - Fasano, A (1997)
The intestinal epithelium represents the major barrier to absorption of orally administered drugs and peptides into the systemic circulation. Entry of molecules through the paracellular pathway is restricted by tight junctions. We have previously reported that these structures can be modulated by Zonula occludens toxin (Zot). In the present report, we show that Zot reversibly increases rabbit intestinal permeability to insulin by 72% (P = 0.034) and immunoglobulins by 52% (P = 0.04) in vitro. When tested in vivo, Zot induced a 10-fold increase of insulin absorption in both the rabbit jejunum and ileum, whereas no substantial changes were detected in the colon. Similar results were obtained with immunoglobulins, whereby Zot induced twofold and sixfold increases of IgG absorption in the jejunum and ileum, respectively. In diabetic rats, bioavailability of oral insulin coadministered with Zot was sufficient to lower serum glucose concentrations to levels comparable to those obtained after parenteral injection of the hormone. The survival time of diabetic animals chronically treated with oral insulin + Zot was comparable to that observed in parenterally treated rats. These studies offer an innovative strategy for the oral delivery of drugs and proteins normally not absorbed through the intestine.